2022
DOI: 10.3390/ijms232213893
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the pH on the Antibacterial Potential and Cytotoxicity of Different Plasma-Activated Liquids

Abstract: In this study, different plasma-activated liquids were evaluated for their antimicrobial effects against Escherichia coli, as well as for their cytotoxicity on mammalian cells. The PALs were prepared from distilled (DIS), deionized (DI), filtered (FIL), and tap (TAP) water. Additionally, 0.9% NaCl saline solution (SAL) was plasma-activated. These PALs were prepared using 5 L/min air gliding arc plasma jet for up to 60.0 min of exposure. Subsequently, the physicochemical properties, such as, the oxidation-reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 89 publications
1
18
0
Order By: Relevance
“…The pH of the PTM remained unchanged after NTAPP, which is identical to our results [ 46 , 47 ]. The DMEM has the capacity to maintain the pH and temperature of the PTM [ 48 ]. Despite whether the effects of the plasma are direct or indirect, the right amount of time must be allowed for irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…The pH of the PTM remained unchanged after NTAPP, which is identical to our results [ 46 , 47 ]. The DMEM has the capacity to maintain the pH and temperature of the PTM [ 48 ]. Despite whether the effects of the plasma are direct or indirect, the right amount of time must be allowed for irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the concentrations of nitrite and nitrate in PAW prepared with tap water were unaffected by the storage time (Figure 8b) because of the absence of acidification and the buffer effect of carbonates in tap water (Wartel et al., 2021). Moreover, it was reported that PAW (pH = 3.5) prepared from tap water performed the best inactivation efficacy against E. coli compared to distilled, deionized, filtered, and saline water as shown in Figure 9 (Sampaio et al., 2022).…”
Section: Microbial Inactivation By Pawmentioning
confidence: 97%
“…Overview of the antibacterial effects of Escherichia coli exposure in contact with plasma-activated water prepared from distilled, deionized, filtered, 0.9% saline and tap water over time at pH = 3.5. Reproduced fromSampaio et al (2022) with the permission of MDPI.…”
mentioning
confidence: 99%
“…APPJs generate plasma plumes in open spaces, enabling the direct treatment of samples of different shapes and sizes [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Over the years, APPJs have been successfully tested in many applications, such as material treatment, sterilization, cancer and wound treatment, aesthetic applications, and dentistry [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Many different configurations of APPJs are reported in the literature.…”
Section: Introductionmentioning
confidence: 99%